2018
DOI: 10.7554/elife.38852
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of cerebellar Purkinje cells facilitates whisker reflex adaptation through increased simple spike activity

Abstract: Cerebellar plasticity underlies motor learning. However, how the cerebellum operates to enable learned changes in motor output is largely unknown. We developed a sensory-driven adaptation protocol for reflexive whisker protraction and recorded Purkinje cell activity from crus 1 and 2 of awake mice. Before training, simple spikes of individual Purkinje cells correlated during reflexive protraction with the whisker position without lead or lag. After training, simple spikes and whisker protractions were both enh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(107 citation statements)
references
References 104 publications
(196 reference statements)
14
93
0
Order By: Relevance
“…More specifically, comparison of the impact of Purkinje cell stimulation on the extent of sensory-induced coherence revealed that Purkinje cells in medial crus 2 and lateral crus 1 differed in their impact on gamma band coherence, but showed no significant difference on theta band coherence. Since these data on regional heterogeneity were based on differential Purkinje cell modulations during different forms of adaptive and reflexive whisking behavior (Romano et al, 2018), they are consistent with the prominent dependency of the gamma, but not theta, band coherence on behavioral context (Fig. 3).…”
Section: Regional Heterogeneity In Cerebello-cerebral Communicationsupporting
confidence: 75%
See 4 more Smart Citations
“…More specifically, comparison of the impact of Purkinje cell stimulation on the extent of sensory-induced coherence revealed that Purkinje cells in medial crus 2 and lateral crus 1 differed in their impact on gamma band coherence, but showed no significant difference on theta band coherence. Since these data on regional heterogeneity were based on differential Purkinje cell modulations during different forms of adaptive and reflexive whisking behavior (Romano et al, 2018), they are consistent with the prominent dependency of the gamma, but not theta, band coherence on behavioral context (Fig. 3).…”
Section: Regional Heterogeneity In Cerebello-cerebral Communicationsupporting
confidence: 75%
“…Air puff stimulation of the whiskers triggers reflexive protraction, the amplitude of which is correlated to cerebellar activity (Brown and Raman, 2018;Romano et al, 2018). This suggests an interaction between cerebellar activity, whisker protraction and wS1-wM1 coherence.…”
Section: Cerebellar Impact On S1-m1 Coherence Depends On Behavioral Cmentioning
confidence: 90%
See 3 more Smart Citations